Electromagnetic Characterization Of Sm-Yig And Sm-Yig-Pvdf Composites Prepared Using Modified Conventional Mixing Oxide Technique - Al-Habashi, Ramadan Masoud (2009)

(untitled)
Samarium substituted-yttrium iron garnet (Sm-YIG) nanoparticles were fabricated via a modified conventional mixing oxides (MCMO) method according to the Y3-xSmxFe5O12 system (0 ≤ x ≤ 3). In this research, utilization of an organic compound (ethanol) and metal oxides in conjunction with mixing the reactants directly without adding water are the key techniques of this method. Using ethanol solution instead of water could produce nanoparticles with better homogeneity and smoother surface structure. Single-phase garnet structure of Sm-YIG nanoparticles was produced at 1350 0C sintering temperature with an average particle size ranged from 25 to 39 nm. XRD results of Sm-YIG samples at x = 2 and 2.5, presented some unknown peaks which speculated to, the time or/and sintering temperature is/are not enough to form the garnet structure phase of the samples. The true density values of 5.245 and 6.221 g.cm-3 were calculated for pure yttrium iron garnet (YIG, x=0) and samarium iron garnet (SmIG, x=3) samples, respectively which reached around 99% of the theoretical density of the samples. Real permittivities of the Sm-YIG samples presented almost flat values ranged from 7 to 10 with loss factors around 0.1 to 0.3, for YIG (x=0) and SmIG (x=3) respectively, within 10 MHz to 1 GHz frequency range. The real permeability value 19.5 is presented by pure YIG at 13.4 MHz and declined rapidly to be around 2 at 1 GHz, and decreased with increasing x. The higher permeability resulted in lower permittivity and vice versa for all the Sm-YIG samples. This work was also carried out to prepare the 10 wt% Sm-YIG in Poly-vinylidene-fluride (PVDF) composite samples and study their electromagnetic properties. Sm-YIG samples prepared via MCMO method, PVDF powder and Ethyl-methyl-ketone (MEK) were used to prepare such composites. High permittivities of composite samples observed at lower frequency range indicated to the heterogeneous conduction in the multiphase structure of the composites. The real permeabilities presented almost flat values through all the range of the frequency from 10 MHz to 1 GHz, with value of 1.06 at x=0 and 1.13 at x=3, for 10 wt% Sm-YIG loading in the composites. MCMO technique appears to be another alternative to the conventional (manufactured) technique, due to the decreasing of the particle size with better homogeneity, high purity, reduction of the cost, and high yield in a nano-scale product compared to other preparations techniques. The numerical optimization method performed using MATLAB program is to estimate the effective complex permittivity and/or permeability of each component of the 10 wt% Sm-YIG-PVDF composite samples. It is found that, the optimum impedance values are very close to the measured ones for each composite. The optimized values of the complex permittivities and permeabilities for both components [Sm-YIG and PVDF] are within the estimated ranges. The optimization process eliminated the difference between the measured impedance and the calculated one from Maxwell-Garnett (MG) formula via a specific objective function. Results of a developed formula based on MG formula with a comparison of various theoretical models including the MG, Looyenga, Bruggeman and Sen-Scala-Cohen, have been carried out and discussed with comparisons to the measurements for the 10 wt% Sm-YIG-PVDF composite samples. This was to calculate the complex permittivity and permeability of such composite materials. The lowest mean error percentage values were detected from the developed MG formula for each composite, which was different from composite to composite depend on the mole fraction x. The developed MG model appears to add a new contribution to the theoretical models to calculate the effective permittivity and permeability of mixture ferrite-polymer materials, due to its accuracy as compared with others.